DICARBOXYLATE ANION RECOGNITION BY A REDOX-RESPONSIVE DITOPIC BIS(COBALTICINIUM) CALIX[4]ARENE RECEPTOR MOLECULE - Beer, P; Drew, M; Hazlewood, C; Hesek, D; Hodacova, J; Stokes, S (1993)
A novel calix[4]arene ditopic anion receptor molecule containing two cobalticinium moieties has been prepared and shown by 1H NMR and cyclic voltammetry to coordinate and electrochemically recognise anions including the dicarboxylate dianion adipate.